(untitled) (Itinera, 2013)
In Rosenkranz’s definition, the grotesque is a particular kind of ugly. In the 20th Century it gain thus its own dignity and we can say that the grotesque is the form of survival for the ugly in our age (also the kitch inherits some aspects). It has moments of disfigurement and vulgarity; it is restless, variegated, it undermines classical cathegories: it appeals to the comic and the tragic, but it also desectaes them. Annie Ubersfeld’s between a “grotesque du rire” and a “grotesque de l’angoisse” is very useful to get the grotesque in Verdi, where the anguish grotesque prevails. I have searched to trace the presence of the ugly and the grotesque primarily in Macbeth, I Masnadieri, Luisa Miller. Rosenkranz states that the ugly, and the grotesque that is part of it, find their emancipation in art, by running from the comic; on the contrary, Verdi makes the comic an element that is functional to the grotesque and the horrible, and to the “scenic truth” that is communicated through them.